Gender Representation in The English Textbook Entitled “Stop Bullying Now” for SMA/ MA/ SMK/ MAK Grade XI - Zahra; Permana, Sudarya; Andayani, Rika (STAIRS: English Language Education Journal, 2024)
Textbooks serve as a primary source of knowledge and play a critical role in shaping students' perceptions of social norms, including gender roles. This raises the need to examine whether textbooks have actively supported gender equity or still reinforce traditional gender stereotypes. This research aims to analyze gender representation in a textbook using a quantitative approach and the gender representation grid developed by Brugeilles and Cromer (2009). The findings reveal a significant dominance of male characters in the representation within the textbook, indicating an imbalance in gender representation within the textbook. Moreover, male characters tend to be assigned roles that align with gender stereotypes prevailing in patriarchal societies. These findings carry significant implications for creating inclusive and diverse learning materials to ensure they reflect gender equality and diversity within society. By understanding and recognizing this imbalance, it is hoped that content developers will be motivated to produce more representative and gender-sensitive materials.